Daya Terima dan Nilai Ekonomi Gizi Camilan “Mata Gajah” Berbasis Tepung Kacang Merah dan Ikan Saluang pada Wanita Usia Subur - Jewel Patricia; Annis Catur Adi (Pusat Riset dan Inovasi Nasional, 2026)
Anemia remains a major nutritional problem among women of reproductive age, primarily caused by micronutrient deficiencies such as iron. The development of nutritious and affordable local-based snack products is a potential strategy to improve nutrient intake. This study aimed to analyze the acceptability and nutritional cost of the traditional snack “Mata Gajah” with substitution of red bean flour (Phaseolus vulgaris L.) and saluang fish powder (Rasbora spp.) among women of reproductive age. This experimental study employed a Completely Randomized Design (CRD) with three formulations: F0 (control), F2 (moderate substitution), and F4 (high substitution). Acceptability was evaluated using a hedonic test (scale 1–5) by 30 untrained panelists based on color, aroma, taste, aftertaste, and texture. Data were analyzed using the Friedman test followed by the Wilcoxon test. Nutritional cost was calculated as the ratio between total production cost and nutrient content. The results showed that all formulations were acceptable, with mean scores ranging from 3.6 to 4.2. Formula F2 demonstrated the best acceptability, with sensory characteristics comparable to the control. Statistical analysis indicated significant differences across all sensory parameters (p<0.05), particularly in F4. In terms of nutritional cost, F2 was the most efficient, with values of Rp217.6/mcg for folate and Rp4,989.6/mg for iron. In conclusion, moderate substitution (F2) provides the best balance between acceptability and nutritional cost, making it a promising alternative nutritious snack for women of reproductive age.